Interleukin (IL)-1 gene polymorphisms: relevance of disease severity associated alleles with IL-1β and IL-1ra production in multiple sclerosis - Hans M. Schrijver; Jaco van As; J. Bart A. Crusius; Christien D. Dijkstra; Bernard M. J. Uitdehaag (Hindawi Limited, 2003)
Background: Multiple sclerosis (MS) is an autoimmune disorder, with a considerable genetic influence on susceptibility and disease course. Cytokines play an important role in MS pathophysiology, and genes encoding various cytokines are logical candidates to assess possible associations with MS susceptibility and disease course. We previously reported an association of a combination of polymorphisms in the interleukin (IL)-1B and IL-1 receptor antagonist (IL−1RN) genes (i.e. IL−1RN allele 2+/IL−1B+3959allele 2−) with disease severity in MS. Extending this observation, we investigated whether IL-1β and IL-1ra production differed depending on carriership of this gene combination.